2019
DOI: 10.1177/1524838019841601
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of the Co-Occurrence of Family Violence: A Meta-Analysis on Family Polyvictimization

Abstract: Objective: The aims of this study are to (a) provide reliable estimates of prevalence rates of family polyvictimization by synthesizing the findings from the existing literature, (b) examine the effect sizes of the impact of one type of family victimization on other types of family victimization, and (c) investigate the correlates of family polyvictimization. Method: Databases of literature published on or before April 2018 were searched. A total of 59 publications met the inclusion criteria and were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 92 publications
5
48
1
5
Order By: Relevance
“…Of the other parental stressors, the most important risk factor remains IPV between parents. Although child maltreatment and IPV are two different forms of family violence, they are known to co-occur and overlap in risk factors between them [18,28]. Although limited studies are currently available for the COVID-19 pandemic, some evidence has shown the impact of natural disasters on family violence, especially those of lower socioeconomic status [29].…”
Section: Discussionmentioning
confidence: 99%
“…Of the other parental stressors, the most important risk factor remains IPV between parents. Although child maltreatment and IPV are two different forms of family violence, they are known to co-occur and overlap in risk factors between them [18,28]. Although limited studies are currently available for the COVID-19 pandemic, some evidence has shown the impact of natural disasters on family violence, especially those of lower socioeconomic status [29].…”
Section: Discussionmentioning
confidence: 99%
“…Parents' likelihood to engage in parent–child aggression that can become abusive is known as child abuse potential (Milner, 1994), which prior work has related to poor couple functioning (Moore & Florsheim, 2008; Tucker, Rodriguez, & Baker, 2017). Couple violence is a risk factor for child abuse, with high rates of co‐occurring IPV and child abuse (Chan et al, 2019). This overlap has been observed in families with young children, as mothers who experienced more psychological aggression—either as perpetrator or victim—with their partner also engaged in more psychological and physical aggression toward their preschooler (Grasso et al, 2016).…”
Section: Spillover From the Couple Relationship To Parenting And Chilmentioning
confidence: 99%
“…Previous studies mainly focused on sociodemographic status and multimorbidity of persons who had high medical and social care needs (Baker et al., 2018; Bunn et al., 2018; Palladino et al., 2016). Furthermore, family dysfunction was a common factor of domestic violence and abuse (Chan et al, 2019; Kageyama et al., 2018; Lino et al., 2019). Despite these issues being thought of as taboo (Simone et al., 2016), a multidisciplinary team approach, social capital factors and community participation were mediating factors for domestic violence and abuse (Cao & Maguire‐Jack, 2016; Isumi et al., 2018; Koga et al., 2020; Lucero et al., 2019; Pillemer et al., 2016).…”
Section: Discussionmentioning
confidence: 99%